Health sector analysis: political economy of decentralised health service provision - MAP Consult; Konung International (POTENCIAR, 2021)
This report offers POTENCIAR and the British High Commission (BHC) an analysis of how power arrangements influence the main social, political, and economic factors in service provision and decentralised governance in Mozambique. The results of the study will be used to refine POTENCIAR’s strategy and approach, as well as the design of PAIs in the health sector. While PAIs address issues across multiple sectors, sector analysis will also consider potential entry points for, as well as barriers to, the improvement of intersectoral coordination and strengthening of citizen participation. Through an analysis of the political economy of the health sector, this report will examine the formal and informal power structures and institutions that influence service provision and the decentralised governance of the health sector. Methodologically, the study is based on a bibliographic and documentary review of governance, decentralisation, and accountability across Mozambique, and the health sector in particular. These data are complemented by interviews with key informants who have knowledge of or actively participate in the health sector. The study is based on the northern province of Nampula, which POTENCIAR has identified for the implementation of its first pro-accountability initiative in the health sector.
Keywords: *non-public; G - Mozambique / Moçambique; GP - Nampula; Health PEA; L - english / inglês; access to services / acesso a serviços; accountability / responsabilização; health - health services / serviços de saúde; health / saúde

Inclusive Land Governance in Mozambique: Good Law, Bad Politics? - Cabral, Lídia; Norfolk, Simon (IDS Working Papers, 2016)
This paper analyses inclusive land governance in Mozambique. It focuses on the country’s legal framework and the DUAT, the right to use and benefit from the land. The DUAT is a distinctive element of the Mozambican legislation that has land as the property of the state but recognises land use rights for occupants and users on the basis of a unitary system of tenure. The challenges of putting in practice what is thought to be one of Africa’s most progressive legal frameworks are discussed. These are set against a context where despite land abundance there are concerns over land grabbing and dispossession of rural communities, which constitute over 70 per cent of the country’s population. The law may be progressive but government politics are not, as an increasingly hegemonic elite controls Mozambique’s political system and resources. In the Mozambican context, we addressed these themes and questions at two levels: the national level that concerns legal frameworks, institutional players, policies and processes, complemented by a focus on land governance practices at the local level. We selected the province of Nampula, in Northern Mozambique, as the focus of our analysis of local practices. The main reason for this choice was the strategic location of the province within the Nacala corridor, an area extending along the transport corridor connecting the Mozambican hinterland to the seaport at Nacala. The Nacala corridor is a region of rapid economic expansion that has been stimulated by the development of the transport network that comprises the railway connecting Nacala to the coal mine explored by Vale in Tete province, one of the largest foreign investments in Mozambique. Unsurprisingly, there has been considerable pressure over land for agriculture, forestry, mining as well as transport infrastructures and the corridor has become a hot spot for some of the most high-profile cases of land conflict in Mozambique (UNAC and GRAIN 2015). Nampula is also one of SDC’s target provinces.
Keywords: *indexed; *tagged; DUAT (Direito do uso e aproveitamento da terra) / Land Use and Benefit Right; G - Mozambique / Moçambique; G - Nacala; G - north / norte; GP - Nampula; L - english / inglês; M - political economy analysis (PEA) / análise de economia política (AEP); Northern PEA; agriculture / agricultura; extractive industries / indústrias extractivas; governance / governação; land governance / gestão de terra; law / direito; ⛔ No DOI found